2016
DOI: 10.3847/0004-637x/822/2/78
|View full text |Cite
|
Sign up to set email alerts
|

The Story of Supernova “Refsdal” Told by Muse*

Abstract: We present Multi Unit Spectroscopic Explorer (MUSE) observations in the core of the Hubble Frontier Fields (HFF) galaxy cluster MACS J1149.5+2223, where the first magnified and spatiallyresolved multiple images of supernova (SN) 'Refsdal' at redshift 1.489 were detected. Thanks to a Director's Discretionary Time program with the Very Large Telescope and the extraordinary efficiency of MUSE, we measure 117 secure redshifts with just 4.8 hours of total integration time on a single 1 arcmin 2 target pointing. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
156
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(168 citation statements)
references
References 68 publications
11
156
1
Order By: Relevance
“…Grillo, e.g., Karman et al 2015, Grillo et al 2016, as well as the release of previously unpublished data on these fields (e.g., Ebeling et al 2014, Gruen et al 2014. Additional HST WFC3 ultraviolet imaging (Alavi et al 2016) and grism spectroscopy (Schmidt et al 2014) are also being obtained for all the Frontier Field clusters.…”
Section: Uvmentioning
confidence: 99%
“…Grillo, e.g., Karman et al 2015, Grillo et al 2016, as well as the release of previously unpublished data on these fields (e.g., Ebeling et al 2014, Gruen et al 2014. Additional HST WFC3 ultraviolet imaging (Alavi et al 2016) and grism spectroscopy (Schmidt et al 2014) are also being obtained for all the Frontier Field clusters.…”
Section: Uvmentioning
confidence: 99%
“…To complete the total mass distribution of the galaxy cluster, three additional mass components are added to describe the cluster dark matter halo on physical scales larger than those typical of the individual cluster members. These cluster halo components are parametrized as two-dimensional pseudo-isothermal elliptical mass profiles (PIEMD as defined by Kassiola & Kovner 1993; see also Grillo et al 2015a).…”
Section: Definition Of the Mass Modelmentioning
confidence: 99%
“…The SN exploded in one arm of an almost face-on spiral galaxy that is multiply imaged and highly magnified by the cluster gravitational potential (z s =1489 and z 0542; d = redshifts from Grillo et al 2015a). Furthermore, the spiral arm hosting SN Refsdal happens to be sufficiently close to a cluster member galaxy that four additional multiple images are formed with average separation of the order of arcseconds, typical of galaxy-scale strong lensing.…”
Section: Introductionmentioning
confidence: 99%
“…Those exposures, collected as part of the Grism Lens-Amplified Survey from Space (GLASS; PI Treu; GO-13459; Schmidt et al 2014;Treu et al 2015), revealed four resolved images of the background SNe arranged in an Einstein cross configuration around an elliptical cluster member. Models of the complex potential of the galaxy cluster and early-type galaxy lens suggest that three of the four images are magnified by up to a factor of ∼10-20 (Grillo et al 2015;Jauzac et al 2016;Kawamata et al 2015;Kelly et al 2015b;Oguri 2015;Sharon & Johnson 2015;Diego et al 2016;Treu et al 2016).…”
Section: Introductionmentioning
confidence: 99%